Römisches Staatsrecht. Theodor Mommsen. - Mommsen, Theodor, 1817-1903 (Cambridge library collection. Classics., 2011)
Theodor Mommsen's influential multi-volume work, first published between 1871 & 1888, is a systematic treatment of the intricate workings of the Roman state. The renowned German scholar proposed an original & sometimes controversial understanding of Roman institutions, based around the categories of 19th-century constitutional law. The Romans themselves never actually codified their complicated body of law, but by applying a historical approach to describe the development of Roman law Mommsen succeeds in making it more accessible to the reader. He systematises the many diverse legal elements upon which the Roman constitution was based & offers a coherent reading of it. Volume 3, Part 2 focuses mainly on the Roman Senate. Mommsen lists the number of senators, the process by which they were elected & their qualifications. He describes the Senate's rights, duties & protocol, & its jurisdiction & influence.